Sentiment Analysis of Consumers for Determining the Packaging Features of Eucalyptus Oil Products - Wilma Latuny; Victor Oryon Lawalata; Daniel Bunga Pailin; Rahman Ohoirenan (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2021)
This study aims to accurately predict eucalyptus oil packaging features and extract the most features to be improved for redesigning eucalyptus oil packaging. This research begins with taking consumer comments using a power query and then processing it using the data mining method and processed using WEKA to find sentiment analysis and accuracy of consumer comments regarding eucalyptus oil products. This study obtained the tendency of comments on each attribute with an assessment of the accuracy for all classes of 83% and each positive sentiment 3% of comments and 57% of comments for negative courses. The sentiment that shows the packaging tends to be normal at 20%, which is interpreted as neutral. This research can provide a suggestion to redesign the packaging based on the commentary sentiment of eucalyptus oil.